SOCIAL INTERACTION AND POLITICAL TRANSFORMATION OF WAHHABI DA'WAH IN LOMBOK - Nazar Naamy; Khairul Aiman Wan Mokhtar, Wan (Universitas Islam Negeri (UIN) Mataram, 2022)
This article will discuss the social interaction and political transformation of Wahabi da'wah groups in the Sasak community of Lombok NTB. This research question is how the interaction and political transformation of da'wah groups is how the process of political transformation of da'wah ideology towards resources and facilities of the Wahabi group. This research uses qualitative methods with a case study approach. The primary data in this study were taken from the field related to social interaction and ideology, religion, politics, da'wah, Wahabi groups towards resources and facilities. This study uses the point of view of George Caspar Homans' exchange theory. In social interactions that occur in society, basically there is always a process of exchange and rational calculation. What is exchanged here is cost, benefit, reward, punishment. The results of this study reveal that the interaction and political transformation of da'wah carried out by the Wahabi community no longer uses the ideology of da'wah, but the ideology of da'wah is just a sweetener or a way of camouflage in its political movement. While the political process of da'wah ideology has transformed towards resources and facilities, the decisive idea is that resources and facilities are distributed in Lombok society so that indirectly the Wahabi community gets rewards from people outside the Wahabi community, namely NU and NW. The reward in question is the transfer of ideology from NU and NW to Wahabi ideology. This is because the transformation of Wahhabism has moved towards the movement of resources and facilities